Fiqh of Intersex Persons in Muslim-Majority Countries: Jordan and Indonesia in Comparative Perspective - Kartikasari, Dina; Nuryasinta, Radhityas Kharisma (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2025)
The legal status of intersex persons (khunthā) poses a significant challenge to the foundational reliance on binary gender classifications within Islamic inheritance law across Muslim-majority countries. Employing a juridical-comparative methodology, this study analyzes Jordan’s Personal Status Law No. 15 of 2019 and Indonesia’s Compilation of Islamic Law (KHI) to illustrate how different legal systems navigate the epistemological tensions among classical Islamic jurisprudence, biological considerations, and normative certainty concerning the legal status of khunthā in contemporary Muslim societies. The findings reveal that Jordan exemplifies a regime of rigid legal formalism, adhering to the Hanafi madhhab’s doctrine of al-aqall (the least part) to preserve procedural certainty, while largely disregarding contemporary medical evidence. In contrast, although Indonesia’s KHI is commonly regarded as grounded in the Shafi’i madhhab, it neither contains explicit provisions governing the inheritance rights of khunthā nor mandates judges to refer to the Shafi’i madhhab in cases of regulatory vacuum, permitting extensive judicial discretion through rechtsvinding (judicial law-finding), resulting in fragmented and unpredictable outcomes. The comparative analysis indicates that Jordan provides certainty that may be medically unjust, whereas Indonesia offers the potential for medical justice that remains legally uncertain. This article advocates for bio-juridical reform in Muslim-majority countries to realign Islamic law with scientifically informed and distributive justice frameworks that better address the needs of marginalized bodies.